Therapeutic response to pazopanib: case report and literature review on molecular abnormalities of aggressive prolactinomas - Medina, Eduardo J.; Zohdy, Youssef M.; Porto, Edoardo; Revuelta Barbero, Juan M.; Bray, David; Maldonado, Justin; Rodas, Alejandra; Mayol, Miguel; Morales, Bryan; Neill, Stewart; Read, William; Pradilla, Gustavo; et al. (Frontiers in Endocrinology, 2023)
Introduction Aggressive prolactinomas (APRLs) pose a significant clinical challenge due to their high rate of regrowth and potentially life-threatening complications. In this study, we present a case of a patient with an APRL who had a trial of multiple therapeutic modalities with the aim to provide a review of molecular abnormalities and management of APRLs by corroborating our experience with previous literature. Methods A total of 268 articles were reviewed and 46 were included. Case reports and series, and studies that investigated the molecular and/or genetic analysis of APRLs were included. Special care was taken to include studies describing prolactinomas that would fall under the APRL subtype according to the European Society of Endocrinology guidelines; however, the author did not label the tumor as “aggressive” or “atypical”. Addiontionally, we present a case report of a 56-year-old man presented with an invasive APRL that was resistant to multiple treatment modalities. Results Literature review revealed multiple molecular abnormalities of APRLs including mutations in and/or deregulation of ADAMTS6, MMP-9, PITX1, VEGF, POU6F2, CDKN2A, and Rb genes. Mismatch repair genes, downregulation of microRNAs, and hypermethylation of specific genes including RASSF1A, p27, and MGMT were found to be directly associated with the aggressiveness of prolactinomas. APRL receptor analysis showed that low levels of estrogen receptor (ER) and an increase in somatostatin receptors (SSTR5) and epidermal growth factor receptors (EGFR) were associated with increased invasiveness and higher proliferation activity. Our patient had positive immunohistochemistry staining for PD-L1, MSH2, and MSH6, while microarray analysis revealed mutations in the CDKN2A and POU6F2 genes. Despite undergoing two surgical resections, radiotherapy, and taking dopamine agonists, the tumor continued to progress. The patient was administered pazopanib, which resulted in a positive response and the patient remained progression-free for six months. However, subsequent observations revealed tumor progression. The patient was started on PD-L1 inhibitor pembrolizumab, yet the tumor continued to progress. Conclusion APRLs are complex tumors that require a multidisciplinary management approach. Knowledge of the molecular underpinnings of these tumors is critical for understanding their pathogenesis and identifying potential targets for precision medical therapy.